Cymbopogon citratus (DC) Stapf (lemongrass) essential oil has anti-Trypanosoma cruzi effect in Balb/c mice - Rojas, Juan (2012)
Objective: To determine anti-Trypanosoma cruzi effect of Cymbopogon citratus essential oil in Balb/c mice. Design: Experimental, prospective study. Setting: Institute of Clinical Research and Institute of Tropical Medicine, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Cymbopogon citrates essential oil; Balb/c albino mice. Interventions: Animals were randomly assigned to six groups (n = 15): infected and untreated (G1), infected and treated with benznidazole 100 mg/kg (G2), infected and treated with essential oil of Cymbopogon citratus 100 mg/kg and 250 mg/kg (G3 and G4, respectively), uninfected and untreated (G5), and uninfected and treated with 250 mg/kg of Cymbopogon citratus (G6). Infection with T. cruzi was conducted with 104 blood trypomastigotes and treatment began on 8th day post infection (dpi) through 28th dpi. Parasitemia was determined by optical microscopy every 2 days in 5 μL of blood drawn from the tail. In dpi 14, 21 and 28, five animals from each group were sacrificed and the heart was removed for pathology study. Main outcome measures: Parasitemia, number of amastigotes nests and inflammatory infiltrates. Results: Cymbopogon citratus essential oil 250 mg/kg/day reduced parasitemia peak significantly from 113.92 ± 25.66 to 74.60 ± 12.37 tripomastigotes/mL (p <0.05). With 100 mg/kg/day there was a reduction to 77.40 ± 14.93 tripomastigotes/mL (p <0.05). There was also reduction in number of amastigotes and inflammatory infiltrates in the heart. Conclusions: Cymbopogon citratus essential oil had anti-Trypanosoma cruzi effect in Balb/c mice as shown by decline in parasitemia, number of amastigotes nests and inflammatory infiltrates.